Enamel glaze inorganic non-stick coating material and application method thereof
By using enamel glaze inorganic materials and specific processes in the non-stick pan coating to form a strong and wear-resistant coating, the existing non-stick pan coating is solved, and the problem of easy decomposition under high temperature conditions and short service life on aluminum pans is achieved, achieving wider applicability and longer service life.
Patent Information
- Application Number
- CN202411787575.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The existing non-stick pan coating is easy to decompose under high temperature conditions, loses its non-stick effect, and may release carcinogens. It has a short service life and poor wear resistance on aluminum pans.
Enamel glaze inorganic non-stick coating materials, including aluminum glaze, silica, metal titanium powder, titanium oxide, sodium feldspar powder, carbon fiber and other components, are used to form a strong and wear-resistant coating through spraying and sintering processes.
This coating is not only suitable for iron cookware, but also for aluminum cookware, which significantly improves service life and wear resistance, reduces organic emissions, and is non-toxic and harmless, environmentally friendly and safe.
Smart Images

Figure CN119592112A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of non-stick pan coatings, and in particular to an enamel glaze inorganic non-stick coating material and an application method thereof. Background Art
[0002] As a household kitchen utensil, the pot provides great help for food processing in daily life, and the emergence of non-stick pots has made life more convenient for everyone. The non-stick pot has a non-stick effect based on a layer of coating on the inner surface of the pot that plays a non-stick role. At present, the non-stick coating of the non-stick pots sold more on the market is generally Teflon coating. The maximum temperature of the reasonable use of this Teflon coating can reach 290℃~300℃. Although it can also meet the national standard test of 3000 times of rubbing with a scouring pad, this pot body is only suitable for bamboo spatulas, wooden spatulas or silicone spatulas, and the non-stick layer is prone to gaps and detachment under external forces. Especially when used under high temperature conditions for a long time, Teflon will also decompose, not only will it lose its non-stick effect, but the decomposition of Teflon will also directly enter the human body through the food cooked in the pot. Early Teflon contains carcinogens. Although there are currently alternative and mitigation products, the decomposed substances are difficult to absorb after entering the human body, and there is still a problem of endangering human health. At the same time, the coating is decomposed at high temperatures, which also leads to a weakening of non-stick properties.
[0003] Therefore, there is a Chinese invention patent application with application publication number CN114479527A that discloses an inorganic non-stick coating material of enamel glaze and its application method. The inorganic coating of enamel glaze is applied to the substrate to form a specific coating structure on the surface of the substrate, which can make the product have excellent non-stick and wear-resistant properties. It has excellent non-stick and wear-resistant properties, and also includes the advantages of inorganic safety and environmental protection, which is more in line with the conditions of environmental protection and pollution-free. However, this inorganic non-stick coating material of enamel glaze is suitable for iron pots, and its scope of use is limited, which is not conducive to large-scale promotion and use. At present, all aluminum pots are organically coated or chemically coated. For frying, iron shovels are often used, and the machine-coated or chemical coating layer will be damaged by the iron shovel, which greatly damages the surface hardness and wear resistance. Organic matter will be discharged during use, which is not conducive to human health. At the same time, the service life of the pot will be greatly reduced. According to this phenomenon, it is necessary to improve the existing technology. Summary of the invention
[0004] 1. Technical issues that need to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides an enamel glaze inorganic non-stick coating material and an application method thereof, which not only solves the problem of being used on a single pot product, but also improves the hardness and wear resistance, greatly extending the overall service life.
[0006] (II) Technical solutions that need to be adopted
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] An inorganic non-stick coating material for enamel glaze comprises the following preparation of the coating: 30% to 40% of aluminum enamel, 20% to 25% of silicon dioxide, 5% to 10% of metal titanium powder, 8% to 10% of titanium oxide, 5% to 10% of albite powder, 1% to 1.5% of carbon fiber, 0.3% to 0.5% of wetting agent, 20% to 30% of pure water, and 0.3% to 0.5% of defoaming agent.
[0009] The present invention also provides a method for applying an inorganic non-stick coating material for enamel, comprising the following process steps:
[0010] (1) Substrate cleaning: The surface of the substrate to be coated is cleaned and cleaned to remove impurities and oil stains;
[0011] (2) Preparation of coating: 30% to 40% of aluminum enamel, 20% to 25% of silicon dioxide, 5% to 10% of titanium powder, 8% to 10% of titanium oxide, 5% to 10% of albite powder, 1% to 1.5% of carbon fiber, 0.3% to 0.5% of wetting agent, 20% to 30% of purified water, and 0.3% to 0.5% of defoaming agent are prepared into coating;
[0012] (3) sandblasting the surface of the substrate in step (1);
[0013] (4) spraying the coating of step (2) on step (3) to form a primer layer, which then needs to be cooled;
[0014] (5) spraying the coating of step (2) on the base coating of step (4) to form a top coating, followed by baking and sintering in sequence, and after sintering, standing to cool;
[0015] (6) Prepare the finished product.
[0016] Preferably, in step (3), corundum is sprayed onto the surface of the substrate using 7 kg to 8 kg of compressed air through a spray gun to form a roughness of Ra2.5 to Ra3.5 on the substrate.
[0017] Preferably, the coating formed in the spraying step (2) can be baked and sintered in sequence, and finally cooled. Specifically, the coating in step (2) is sprayed on the surface of step (3) with a spray gun at 0.5MPa to 1.0MPa, and the thickness of the primer layer is 40um to 60um, and the baking temperature is ≤300°C after 3 minutes to 5 minutes, and then it is sintered at 450°C to 600°C for 5 minutes to 8 minutes, and finally cooled.
[0018] Preferably, the specific method of step (5) is: spray the coating in step (2) on the surface of step (3) with a spray gun at 0.5MPa~1.0MPa, and the thickness of the top coating is 30um~40um, and then baked at 200℃~260℃ for 3 minutes to 5 minutes, and then sintered at 450℃~600℃ for 5 minutes to 8 minutes, and then cooled and sanded.
[0019] Preferably, the specific method of step (5) is: spray the coating of step (2) directly on the base coating of step (4) to form a top coating, the base coating is in a wet state, and then spray the coating of step (2) by wet spraying to form a top coating, followed by baking and sintering in sequence. After sintering is completed, let it stand to cool, and wipe or sand the surface as needed.
[0020] Preferably, specifically, the coating in step (2) is sprayed on the surface of the base coating in step (4) with a spray gun at 0.5MPa to 1.0MPa, and the thickness of the top coating is 30um to 40um, and then baked at 200℃ to 260℃ for 3 minutes to 5 minutes, and then sintered at 450℃ to 600℃ for 5 minutes to 8 minutes, and then cooled and sanded.
[0021] (III) Technical effects to be achieved
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] First, the aluminum porcelain glaze of the present invention comprises 30% to 40%, silicon dioxide 20% to 25%, metal titanium powder 5% to 10%, titanium oxide 8% to 10%, sodium feldspar powder 5% to 10%, carbon fiber 1% to 1.5%, wetting agent 0.3% to 0.5%, pure water 20% to 30%, and defoaming agent 0.3% to 0.5%. This coating is suitable not only for iron cookware, but also for aluminum cookware, has a wider range of use, and is convenient for large-scale promotion and use.
[0024] Secondly, the production process of the present invention makes the surface hardness and wear resistance of the substrate better, and enhances the service life. Compared with the prior art, the service life of the substrate can be increased by more than 5 times, which is more conducive to meeting the use requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a schematic diagram of a method for applying an inorganic non-stick coating material for enamel glaze.
[0026] Figure 2 The present invention is a schematic block diagram of an embodiment of a method for applying an inorganic non-stick coating material for enamel glaze.
[0027] Figure 3 The present invention is a schematic block diagram of a second embodiment of a method for applying an inorganic non-stick coating material for enamel glaze. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] Embodiment 1: An inorganic non-stick coating material for enamel glaze, comprising the following steps to prepare the coating:
[0030] Aluminum glaze 30% ~ 40%, silicon dioxide 20% ~ 25%, metallic titanium powder 5% ~ 10%, titanium oxide 8% ~ 10%, albite powder 5% ~ 10%, carbon fiber 1% ~ 1.5%, wetting agent 0.3% ~ 0.5%, pure water 20% ~ 30%, defoaming agent 0.3% ~ 0.5%.
[0031] Embodiment 2: It can be explained on the basis of embodiment 1, such as Figure 1 As shown, the present invention also provides a method for applying an enamel inorganic non-stick coating material, comprising the following process steps:
[0032] (1) Substrate cleaning: The surface of the substrate to be coated (the pot or pot embryo) is cleaned to remove impurities and oil stains;
[0033] (2) Preparation of coating: 30% to 40% of aluminum enamel, 20% to 25% of silicon dioxide, 5% to 10% of titanium powder, 8% to 10% of titanium oxide, 5% to 10% of albite powder, 1% to 1.5% of carbon fiber, 0.3% to 0.5% of wetting agent, 20% to 30% of purified water, and 0.3% to 0.5% of defoaming agent are prepared into coating;
[0034] (3) sandblasting the surface of the substrate (i.e., the pot embryo) in step (1);
[0035] Among them, emery (80 mesh, effectively improving wear resistance and durability) is sprayed on the surface of the substrate (cookware, also known as the pot embryo) through a spray gun using 7 kg to 8 kg of compressed air, forming a roughness of Ra2.5 to Ra3.5 on the substrate (cookware, also known as the pot embryo), which is beneficial to increase the adhesion of the subsequent coating layer.
[0036] (4) spraying the coating of step (2) on step (3) to form a primer layer, which then needs to be cooled;
[0037] like Figure 1 As shown, it is further explained that the coating formed in the spraying step (2) can be baked and sintered in sequence, and finally cooled down, wherein the coating in step (2) is sprayed on the surface of step (3) with a spray gun at 0.5MPa~1.0MPa, and the thickness of the primer layer is 40um~60um, and the baking temperature (low-temperature baking) after 3 minutes to 5 minutes is ≤300℃, which can be 200℃~260℃ or 300℃, which greatly increases the bonding strength between the surface of the substrate (cooker, that is, pot embryo) and the subsequent coating micro-nanoporous layer. After the primer layer is dried at 300℃, different temperatures are adjusted according to different substrates (cookers, that is, pot embryos), and then sintered (depending on the substrate, the sintering temperature is between 450℃ and 600℃) for 5 minutes to 8 minutes, and finally cooled down.
[0038] (5) spraying the coating of step (2) on the base coating of step (4) to form a top coating, followed by baking and sintering in sequence. After sintering, the base coating is left to cool and the surface is wiped or sanded as required;
[0039] Further explanation, such as Figure 1 As shown, the coating in step (2) is sprayed on the surface of step (3) with a spray gun at 0.5MPa to 1.0MPa, and the thickness of the top coating is 30um to 40um, and then baked at 200℃ to 260℃ for 3 minutes to 5 minutes, and then sintered (depending on the substrate, the sintering temperature is between 450℃ and 600℃) for 5 minutes to 8 minutes, and then cooled and sanded; or, Figure 2 As shown, the coating of step (2) is directly sprayed on the base coating of step (4) to form a top coating, wherein the base coating is in a wet (not dry) state, and then the coating of step (2) is sprayed by wet spraying to form a top coating, followed by baking and sintering in sequence. After sintering, it is left to cool, and the surface is wiped or sanded as required. Specifically, the coating of step (2) is sprayed on the surface of the base coating of step (4) by a spray gun with 0.5MPa~1.0MPa, and the thickness of the top coating is 30um~40um, and then it is baked at 200℃~260℃ for 3 minutes to 5 minutes, and then sintered (depending on the substrate, the sintering temperature is between 450℃~600℃) for 5 minutes to 8 minutes, and then cooled and sanded.
[0040] According to different substrates (cookware, i.e. pot embryos), baking and sintering at different temperatures of 450℃ to 600℃ and sintering for different times of 3 minutes to 8 minutes can produce micro-nano pores on the surface of the topcoat. The micro-nano pore layer of the spray coating is mainly to improve the surface hardness and wear resistance of the topcoat, so that tiny pores are formed on the surface of the topcoat, which can store edible oils and fats on the pore surface of the substrate (cookware, i.e. pot embryo) during the first use of the substrate (cookware, i.e. pot embryo), thereby forming an oil film to achieve the purpose of non-stick food. For baking and sintering, the micro-nano pores of the spray coating are formed through different sintering according to different substrates (cookware, i.e. pot embryos) materials and shapes. The temperature is adjusted between 450℃ and 600℃, and it must also be adjusted at different sintering times of 3 minutes to 8 minutes. After the sintering time is controlled at 450℃ to 600℃, tiny micro-nano oil storage pores will appear on the surface of the top coating, which can produce an oil film on the surface of the base material (the pot embryo) during maintenance or after use, making the pot have a long-lasting non-stick function.
[0041] (6) Prepare the finished product.
[0042] The present invention is not only suitable for iron pots, but also for aluminum pots, and can also be used on metals such as iron, aluminum, magnesium, stainless steel, stainless iron, three-layer steel, two-layer steel, or copper, which greatly improves the scope of use. In the prior art, the non-stick performance of the coating on aluminum pots is short, and the use time of different performances cannot exceed 1 to 4 months. The coating used in the present invention is an inorganic material, which is non-toxic, harmless, healthy and environmentally friendly. It not only solves the problem of short non-stick durability of organic coatings, but also improves the surface hardness and wear resistance of the coating layer. Therefore, even if a shovel is used for collision, there will be no damage to the substrate (pot, that is, pot embryo). The emission of organic matter can be reduced during the production process, which is safer and more environmentally friendly, and does not cause pollution to the environment. The present invention increases the service life of the substrate (pot, that is, pot embryo), which can increase the service life of the substrate (pot, that is, pot embryo) by more than 5 times, and can better meet the use requirements.
[0043] It should be noted that, although the above embodiments have been described in this article, the scope of patent protection of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields are all included in the scope of protection of the patent of the present invention.
Claims
1. An inorganic non-stick enamel coating material, characterized in that: The coating is prepared as follows: 30% to 40% aluminum glaze, 20% to 25% silicon dioxide, 5% to 10% metal titanium powder, 8% to 10% titanium oxide, 5% to 10% sodium feldspar powder, 1% to 1.5% carbon fiber, 0.3% to 0.5% wetting agent, 20% to 30% pure water, and 0.3% to 0.5% defoaming agent.
2. A method for applying an inorganic non-stick coating material for enamel, characterized in that: The process steps include: (1) Substrate cleaning: The surface of the substrate to be coated is cleaned and cleaned to remove impurities and oil stains. (2) Coating preparation: 30% to 40% of aluminum enamel, 20% to 25% of silicon dioxide, 5% to 10% of metal titanium powder, 8% to 10% of titanium oxide, 5% to 10% of sodium feldspar powder, 1% to 1.5% of carbon fiber, 0.3% to 0.5% of wetting agent, 20% to 30% of purified water, and 0.3% to 0.5% of defoaming agent are prepared into a coating; (3) sandblasting the surface of the substrate in step (1); (4) spraying the coating of step (2) on step (3) to form a primer layer, which then needs to be cooled; (5) spraying the coating of step (2) on the base coating of step (4) to form a top coating, followed by baking and sintering in sequence, and after sintering, standing to cool; (6) Prepare the finished product.
3. The method for applying the enamel inorganic non-stick coating material according to claim 2, characterized in that: In step (3), corundum is sprayed onto the surface of the substrate using 7 kg to 8 kg of compressed air through a spray gun, forming a roughness of Ra2.5 to Ra3.5 on the substrate.
4. The method for applying the enamel inorganic non-stick coating material according to claim 2, characterized in that: The coating formed by spraying step (2) can be baked and sintered in sequence, and finally cooled down. Specifically, the coating in step (2) is sprayed on the surface of step (3) with a spray gun at 0.5MPa to 1.0MPa, and the thickness of the primer layer is 40um to 60um, and the baking temperature is ≤300°C after 3 minutes to 5 minutes, and then sintered at 450°C to 600°C for 5 minutes to 8 minutes, and finally cooled down.
5. The method for applying the enamel inorganic non-stick coating material as claimed in claim 2, 3 or 4, characterized in that: The specific method of step (5) is as follows: the coating of step (2) is sprayed on the surface of step (3) by a spray gun at 0.5MPa to 1.0MPa, and the thickness of the top coating is 30um to 40um, and then baked at 200℃ to 260℃ for 3 minutes to 5 minutes, and then sintered at 450℃ to 600℃ for 5 minutes to 8 minutes, and then cooled and sanded.
6. The method for applying the enamel inorganic non-stick coating material according to claim 2 or 3, characterized in that: The specific method of step (5) is as follows: the coating material of step (2) is directly sprayed on the base coating layer of step (4) to form a top coating layer, the base coating layer is in a wet state, and then the coating material of step (2) is sprayed by wet spraying to form a top coating layer, followed by baking and sintering in sequence. After sintering is completed, it is left to cool and the surface is wiped or sanded as required.
7. The method for applying the enamel inorganic non-stick coating material according to claim 6, characterized in that: Specifically, the coating in step (2) is sprayed on the surface of the base coating in step (4) with a spray gun at 0.5MPa to 1.0MPa, and the thickness of the top coating is 30um to 40um, and then baked at 200℃ to 260℃ for 3 minutes to 5 minutes, and then sintered at 450℃ to 600℃ for 5 minutes to 8 minutes, and then cooled and sanded.
Citation Information
Patent Citations
Enamel glaze inorganic non-stick coating material and application method thereof
CN114479527A